Risk of HIV infection among male sex workers in Spain - Belza, M (BMJ Group, 2005)
Objective: To assess HIV prevalence and predictive factors for HIV among male sex workers in Spain. Methods: In this study we analysed all male sex workers who visited HIV testing clinics in 19 Spanish cities between 2000 and 2002. The information was obtained during examination by means of a brief questionnaire. For repeating testers, only the last confirmed result was taken into account. Results: 418 male sex workers were included in the analysis; 58% visited these clinics for the first time and 42% were repeating testers. 67% were of foreign origin, mostly from Latin America (91%). 96% had had sex with men, 18% were transvestites or transsexuals, and 3.3% had used injected drugs. HIV prevalence was 12.2% (95% CI, 9.3 to 15.8%), and rose to 16.9% among first time testers. No differences in HIV prevalence were found between injecting drug users, transvestites/transsexuals, and men from foreign countries. Conclusion: Because of the high risk of HIV infection, male sex workers should be the target of specific preventive activities. Preventive and healthcare strategies that are culturally adapted to migrants are required.